A strongly complexed solid polymer electrolyte enables a stable solid state high-voltage lithium metal battery. Issue 12 (24th October 2022) - Wang, Hangchao; Song, Jin; Zhang, Kun; Fang, Qiu; Zuo, Yuxuan; Yang, Tonghuan; Yang, Yali; Gao, Chuan; Wang, Xuefeng; Pang, Quanquan; Xia, Dingguo
Abstract : Bi-functional N -methylurea molecules participate in co-solvating the Li + ions enhancing the ionic conductivity, and deactivate the non-solvating polymer ethereal groups through the amide acceptor, providing a wide electrochemical window. Abstract : A solid-state electrolyte with a wide electrochemical window, high Li-ion conductivity, and anti-dendritic growth properties are required for high-energy-density solid-state batteries. Here, we reported a polyglycol oxide-based solid electrolyte constructed by incorporating a deep eutectic solvent within a dual crosslinked network. The combination of N -methylurea shielding the active ether group in the polyglycol chain and the quadruple hydrogen bond interactions result in the formation of an all solid polyglycol oxide-based electrolyte (ASPE) with an electrochemical window of 5.2 V. The newly developed ASPE demonstrates high ionic conductivity, uniform Li deposition, and high Li plating/stripping efficiencies. Facile in situ polymerization applications of ASPE in Li–LiFePO4, Li–LiCoO2, and Li–Li1.2 Ni0.13 Co0.13 Mn0.54 O2 batteries further show the diversity of the ASPE and its ability to achieve a high Coulombic efficiency and long life. Our finding deviates from the conventional wisdom of designing polymer electrolytes, demonstrating a promising direction for safe, high-energy, and long-life solid-state Li metal batteries.